Does it cost more to train residents or to replace them? : a look at the costs and benefits of operating graduate medical education programs - Wynn, Barbara O.; Smalley, Robert; Cordasco, Kristina M. (Research report (Rand Corporation), 2013)
Medicare is the primary vehicle for federal support for physician residency training programs through its graduate medical education payments to teaching hospitals. One important factor influencing the decisions that a teaching hospital makes regarding graduate medical education (GME) program offerings is how the residency programs are likely to affect its financial performance. The Medicare Payment Advisory Commission (MedPAC) is concerned that the increasing trend toward physician specialization is inconsistent with the needs of an efficient, high-quality, high-value health care delivery system for primary care physicians (MedPAC, 2010). MedPAC asked RAND to use available literature and data to summarize how the costs and benefits of operating residency training programs are likely to vary by specialty. The underlying policy question is whether Medicare support for residency training programs should be restructured to differentiate between programs that are less costly or self-sustaining and those that are more costly to the supporting institution.